1993
DOI: 10.1073/pnas.90.2.422
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced intrachromosomal recombination in plant somatic cells.

Abstract: Levels of induced homologous recombination between chromosomal repeats in plant somatic cells were examined. Transgenic plants of Nicotiana tabacum hemi-or homozygous for pairs of deletion derivatives of the neomycin phosphotransferase (nptI) marker gene integrated at a single genomic locus were produced. Homologous recombination within the overlapping parts of the nptll gene restored the function and the resulting kanamycin resistance was used for scoring recombination frequency. The recombination events were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
70
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 32 publications
7
70
0
Order By: Relevance
“…It has been shown that in plants homologous recombination can be stimulated by genomic stress caused by x-rays, mitomycin C, and MMS treatments (9)(10)(11). This indicates that homologous recombination is involved, at least in part, in the repair of the DNA damage caused by these agents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that in plants homologous recombination can be stimulated by genomic stress caused by x-rays, mitomycin C, and MMS treatments (9)(10)(11). This indicates that homologous recombination is involved, at least in part, in the repair of the DNA damage caused by these agents.…”
Section: Discussionmentioning
confidence: 99%
“…As in other organisms (5), the frequency of meiotic recombination in plants is influenced by environmental factors (6), sequence diversity in interspecific crosses (7), and the direction of crossing (8). In somatic cells, rates of homologous recombination can be stimulated by DNA-damaging treatments (9)(10)(11). This also has been observed in bacteria, yeast, and mammalian cells (12).…”
mentioning
confidence: 88%
See 3 more Smart Citations